Investigation of mixing performance and safety characteristics of polymer-based energetic materials simulant via screw-pressing blending extrusion charges - Gaoming Lin; Huzeng Zong; Suwei Wang; Huang Chen; Siyu Yu; Xiaojie Hao; Kang Wang; Yuanyuan Li; Guohui Zhang (Defence Technology)
The present study introduces a screw-pressing charging method to tackle deficiencies in automation and charge uniformity during the melt-casting of polymer-based energetic materials. To ensure the safety of the experiments, this study used inert materials with similar physical properties to partially substitute for the actual energetic components in the preparation of simulant materials. By thoroughly analyzing slurry physical properties, a simulation framework and an extensive performance evaluation method were developed. Such tools guide the design of the structure and configuration of process parameters. Results demonstrate that employing the Pin element significantly enhances radial mixing within the screw, minimizes temperature variations in the slurry, and improves both efficiency and safety in the mixing process. Further, adjustments such as widening the cone angle of the barrel, modifying the solid content of the slurry, and varying the speed of the screw can optimize the mechanical and thermal coupling in the flow field. These adjustments promote higher-quality slurry and create a safer production environment for the extrusion process.